2015
DOI: 10.1589/jpts.27.2307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different hand positions on trunk and shoulder kinematics and reaction forces in sitting pivot transfer

Abstract: [Purpose] The purpose of this study was to compare the changes in trunk and shoulder angles, and reaction forces under the two hands elicited by different hand base of support positions during sitting pivot transfer. [Subjects and Methods] Eighteen unimpaired subjects performed independent sitting pivot transfer. Subjects performed sitting pivot transfer between an initial seat to a target seat by only using their hands positioned at the same height as and lower than the seat position. Trunk and shoulder kinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, with regard to transfer movement in confined spaces such as CT movement, it has been suggested that the magnitude of the hip flexion angle affects smooth movement of the buttocks. Kim et al compare the changes in the trunk and shoulder angles and reaction forces under the two hands elicited by different hand base-of-support positions during sitting pivot transfer10 ) . They reported that the lower hand position should be recommended as an effective and safe method for sitting pivot transfer for patients with spinal cord injury, because this position was associated with a significantly high trunk angle of forward and lateral flexion, even though the angle of rotation while transferring to the 20-cm lower support position was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…However, with regard to transfer movement in confined spaces such as CT movement, it has been suggested that the magnitude of the hip flexion angle affects smooth movement of the buttocks. Kim et al compare the changes in the trunk and shoulder angles and reaction forces under the two hands elicited by different hand base-of-support positions during sitting pivot transfer10 ) . They reported that the lower hand position should be recommended as an effective and safe method for sitting pivot transfer for patients with spinal cord injury, because this position was associated with a significantly high trunk angle of forward and lateral flexion, even though the angle of rotation while transferring to the 20-cm lower support position was reduced.…”
Section: Discussionmentioning
confidence: 99%